Toward Elucidating Epigenetic and Metabolic Regulation of Stem Cell Lineage Plasticity in Skin Aging - Lyu, Ying; Ge, Yejing (Frontiers in Cell and Developmental Biology, 2022)
Skin is the largest organ in human body that harbors a plethora of cell types and serves as the organismal barrier. Skin aging is graphically pronounced such as wrinkling and hair graying, and the molecular mechanisms behind these phenotypic manifestations are beginning to unfold. Similar to many other organs and tissues, epigenetic and metabolic deregulations emerge as key aging drivers. Particularly in the context of the skin epithelium, the epigenome and metabolome coordinately shape lineage plasticity and orchestrate stem cell function during aging. Our review discusses recent studies that proposed molecular mechanisms that drive the degeneration of hair follicles, a major appendage of the skin. By focusing on skin while comparing to other model systems and adult stem cells, we summarize literature on genotoxic stress, nutritional sensing, metabolic rewiring, mitochondrial activity, and epigenetic regulations of stem cell plasticity. Finally, we speculate the rejuvenation potential in respect to the rate-limiting upstream signals during aging and the dominant role of tissue microenvironment in dictating aged stem cell function.